Non-fungible token (NFT) as a future asset in Islamic wealth management / Assoc. Prof. Dr Amirul Afif Muhamat - Muhamat, Amirul Afif (Office of the Deputy Vice-Chancellor (Research & Innovation), 2023)
The Islamic finance industry is rapidly expanding worldwide, fueled by the latest and distinctive innovation known as Fintech, which incorporates Artificial Intelligence (AI) into the financial landscape via the internet. Islamic finance is projected to outpace its conventional counterpart in several Muslim-majority countries, including Saudi Arabia, Malaysia, Indonesia, and others. Dinar Standard, a boutique Islamic finance research firm, has compiled a Global Islamic Fintech Index, placing Malaysia and Saudi Arabia at the forefront, followed by Indonesia, the United Kingdom (UK), and the United Arab Emirates (UAE). The estimated income generated via Islamic fintech is expected to reach USD 179 billion by 2026. As the Fintech sector expands, Islamic wealth management, a vital component of Islamic finance, is gaining prominence. This sector of the market has been saturated with traditional financial products over the years. However, the increasing popularity of Non-Fungible Tokens (NFTs) has revealed a business potential that Islamic financial institutions should explore. NFTs are another type of Fintech product created using blockchain technology, a unique digital data store that cannot be easily replicated or tampered with. This distinctive property of NFTs makes them promising financial assets.